“Tratado” e Exercício de ser criança: a infância entre versos, rimas e tintas - Penha Lucilda de Souza Silvestre; Alice Áurea Penteado Martha (Estudos de Literatura Brasileira Contemporânea)
The work of art, in general, consists of a significant event, considering the reader can experience different fictional worlds, as well as retrieve and articulate the intertextual networks in the act of reading. Thus, there is the possibility of rethinking one’s own experience as well as the social conditions in which the child is inserted. In this sense , our objective is to perform a journey through the poetic universe from the reading of the texts Exercício de ser criança (1999), by Manoel de Barros, and Um pequeno tratado de brinquedos para meninos quietos (2009), by Selma Maria Kuasne, associating the m to the paintings by Candido Portinari, ‘Boys flying kites’ (1932), ‘Children playing’ (1938) and ‘Boys playing’ (1955). Indeed, these pictures enable us to rethink how the representation and the constitution of childhood in art are conceived and to under stand them in the weaving of poetry and painting, as well as the act of playing, in a dialectical process.